Total Water Intake and Urine Measures of Hydration in Adult Dogs Drinking Tap Water or a Nutrient-Enriched Water - Zanghi, Brian M.; Gardner, Cari L. (Frontiers in Veterinary Science, 2018)
Water intake and urine measures were evaluated in dogs offered tap water (TW) or a nutrient-enriched water (NW) supplement while fed dry food with ad libitum TW in a bucket. Baseline (day-7) urine specific gravity (USG) was analyzed from healthy, adult small breed dogs (n=21; 2-11 years). Dogs (N=16) were selected with ≥1.015 USG, then equally divided into 2 groups balanced for USG. Groups received either TW or NW in a bowl for 56 days. Dose for each dog was 0.5:1 or 2:1 water-to-calorie ratio (mL:kcal ME/d) from days 1-49 or 50-56, respectively, based on baseline calorie intake. Daily food calorie and total liquid intake (TLI; g/d; sum of NW or TW in a bowl and bucket water) was used to calculate weekly intake and USG measured on days -7, 14, 42, 56. Calorie intake was not different (P>0.49). A significant (P<0.001) time-by-treatment interaction resulted for TLI with baseline similar between groups and no difference between weeks for the TW group. Following baseline, NW group had increased (P<0.05) TLI every week, except for week 2 (P=0.07). A significant (P<0.002) time-by-treatment interaction resulted for USG, with baseline similar between groups and no difference between sampling days for the TW group (varied by ≤0.006 g/mL), whereas NW group was lower (P<0.01) on days 42 (1.018 g/mL) and 56 (1.014 g/mL) versus baseline (1.026 g/mL). This study indicates that all dogs offered the NW supplement increased their TLI and produced a more dilute urine, which suggests an improvement in overall hydration.